Probiotic Effects Against Viral Respiratory Infections: A Novel Approach to an Old Problem - Rana Tafrishi; Hamid Ahanchian; Javad Ghaffari (Journal of Pediatrics Review)
Background: Upper respiratory tract infections (URTI) are the most common human illnesses, leading to high absenteeism from school and work. Objectives: Although the importance of viral respiratory infections is known, preventive strategies are not yet well understood, so this study aims to investigate the preventive strategies. Methods: Several studies have confirmed that probiotics can reduce the frequency, duration and severity of upper respiratory tract infections. Results: Probiotic consumption was also associated with a significant reduction in school absenteeism and antibiotic prescription, as well as a significant decrease in fever (OR=0.19), cough (OR=0.14) and rhinorrhea episodes (OR=0.18). However, few clinical trials have investigated the effects of probiotics or synbiotics on specific viruses. Conclusions: Further research is needed to determine the role of probiotics and prebiotics, especially postbiotics, in the treatment and prevention of respiratory infections. This study aimed to review the effect of probiotics against various viruses.